2020
DOI: 10.1093/pm/pnaa213
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Pain-Related 30-Day Emergency Department Return Visits in Middle-Aged and Older Adults

Abstract: Objective The objective of this study was to determine predictive factors for pain-related emergency department returns in middle-aged and older adults. Design, Setting, and Subjects. This was a subanalysis of patients > 55 years of age enrolled in a prospective observational study of adult patients presenting within 30 days of an index visit to a large, urban, academic center. Methods Demographic and clinical data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Although previous evidence reached consensus that older adults encountered more ED returns when compared with younger adults, the increasing age, within the spectrum of the older population, has yet demonstrated contradictory results. Some studies coincided with our finding that the oldest old were less prone to re-visit, [33][34][35] whereas others concluded that the likelihood of returning to EDs increased concurrently with advancing age. 5,11,13,28 Such inconsistencies in the age effect highlight the importance of considering factors that can more accurately reflect biological or functional age (eg, frailty) rather than simply chronological age in the geriatric population evaluation.…”
Section: Discussionsupporting
confidence: 85%
“…Although previous evidence reached consensus that older adults encountered more ED returns when compared with younger adults, the increasing age, within the spectrum of the older population, has yet demonstrated contradictory results. Some studies coincided with our finding that the oldest old were less prone to re-visit, [33][34][35] whereas others concluded that the likelihood of returning to EDs increased concurrently with advancing age. 5,11,13,28 Such inconsistencies in the age effect highlight the importance of considering factors that can more accurately reflect biological or functional age (eg, frailty) rather than simply chronological age in the geriatric population evaluation.…”
Section: Discussionsupporting
confidence: 85%
“…To review the scope of the challenges that vulnerable populations are facing, Charleston and colleagues in 2018 argued that underrepresented minority patients encounter numerous healthcare barriers, including lack of access, insurance coverage of treatment, transportation to and from appointments, and prohibitive costs [ 18 ]. A recent study conducted by Sheikh and colleagues in 2020 examining predictive factors for pain-related ED returns in middle-aged and older adults, revealed that African Americans who return to the ED for pain have low health literacy [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NRS predicting ED administration of opioid medications in our patient sample demonstrates the power of pain scales to influence pain management, specifically opioid administration, in acute care settings like the ED. Others have also reported associations between unidimensional pain scales and increased analgesia administration and opioid adverse events [ 14 , 15 ]. Our results of increasing NRS pain category severity predicting ED opioid administration and DVPRS differentiating between moderate and high levels of pain coupled together suggest that patients may receive fewer opioid medications in the ED if the DVPRS (and not NRS) is used to measure pain intensity.…”
Section: Discussionmentioning
confidence: 99%
“…This study was a secondary analysis of data collected from the University of Florida Institutional Review Board-approved prospective observational study of 389 patients ≥18 years of age returning to the ED within 30 days of an initial (index) visit (Figure 1 ). Full study details have been published previously [ 15 , 16 ]. Briefly, all community-dwelling adult patients reporting to our ED and able to provide consent were eligible for inclusion.…”
Section: Methodsmentioning
confidence: 99%